Examining Truth and State-Sponsored Media Campaigns as a Means of Decreasing Youth Smoking and Related Disparities in the United States. Issue 4 (29th October 2021) - Colston, David C; Xie, Yanmei; Thrasher, James F; Patrick, Megan E; Titus, Andrea R; Emery, Sherry; McLeod, M Chandler; Elliott, Michael R; Fleischer, Nancy L
Abstract: Introduction: To analyze the impact of Truth and state-sponsored anti-tobacco media campaigns on youth smoking in the United States, and their potential to reduce tobacco-related health disparities. Aims and Methods: Our study included data from the 2000–2015 Monitoring the Future study, an annual nationally representative survey of youth in 8th (n = 201 913), 10th ( n = 194 468), and 12th grades ( n = 178 379). Our primary exposure was Gross Rating Points (GRPs) of Truth or state-sponsored anti-tobacco advertisements, from Nielsen Media Research. Modified Poisson regression was used to assess the impact of a respondent's GRPs on smoking intentions, past 30-day smoking participation, and first and daily smoking initiation. Additive interactions with sex, parental education, college plans, and race/ethnicity were used to test for differential effects of campaign exposure on each outcome. Results: Greater campaign exposure (80th vs. 20th GRP percentile) was associated with lower probabilities of smoking intentions among 8th graders, smoking participation among 8th and 12th graders, and initiation among 8th graders. Greater exposure was associated with a greater reduction in the likelihood of smoking participation among 10th and 12th grade males than females; 10th and 12th graders with parents of lower education versus those with a college degree; and 12th graders who did not definitely plan to go to college relative to those who did. Conclusions: Media campaign exposure was associated with a lower likelihood of youth smoking behaviors. Associations were more pronounced for groups disproportionately affected by smoking, including youth of lower socioeconomic status. Media campaigns may be useful in reducing smoking disparities and improving health equity. Implications: Few recent studies have investigated the impact of anti-tobacco media campaigns on youth smoking and their potential to reduce tobacco-related health disparities in the United States. We found media campaigns—specifically state-sponsored media campaigns—reduced the likelihood of several smoking outcomes among youth, with some evidence that they mitigate disparities for disproportionately affected groups.